Correction: Formation of reactive aldehydes (MDA, HHE, HNE) during the digestion of cod liver oil: comparison of human and porcine in vitro digestion models. Issue 12 (6th December 2017) - Tullberg, Cecilia; Larsson, Karin; Carlsson, Nils-Gunnar; Comi, Irene; Scheers, Nathalie; Vegarud, Gerd; Undeland, Ingrid
Abstract : Correction for 'Formation of reactive aldehydes (MDA, HHE, HNE) during the digestion of cod liver oil: comparison of human and porcine in vitro digestion models' by Cecilia Tullberg et al., Food Funct., 2016, 7, 1401–1412.